Biodiversity associated with the rocky and sandy intertidal zone of El Pelado Beach, Ecuador - Quijije Franco, Genny Andrea; Kuonqui Fernandez, Ana Sofia; Delgado Jimenez, Jose Alexander; Ochoa Herrera, Jean Piere; Morales Ramos, Félix Enrique (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2025)
Coastal ecosystems are characterized by the presence of the intertidal zone, whose environmental factors are dynamic and depend on high and low tide periods. In this research, we analyzed the biodiversity associated with the rocky and sandy intertidal zone of El Pelado beach, Ecuador. Sampling was conducted in three transects for each type of substrate, measuring physicochemical parameters and recording organism abundance. Limited species diversity was found in the sandy substrate, including two isopods, a starfish, a bivalve, a gastropod and an annelid. Additionally, a temperature range of 26.1 °C to 38.8 °C was recorded according to the distance from the sea. The rocky substrate showed greater biodiversity, especially in tide pools, where temperature variations from 26.8 °C to 31.2 °C and salinity ranging from 32.0 to 33.2 PSU were recorded. Different organism distribution zones were identified: the lower intertidal zone dominated by algae genus (Ulva, Ceramium), the middle zone with a predominance of Balanus, and the upper zone with abundant goose barnacles and mussels. Ecological interactions were more evident in the rocky substrate, highlighting the epibiotic relationship between mussels and barnacles. The results demonstrate that differences in the physical characteristics of both substrates determine the composition and structure of benthic communities, with the rocky substrate showing greater diversity-
Keywords: Intertidal zone; marine biodiversity; physicochemical parameters, rocky platform; sandy substrate; tide pools